DAMPAK COVID-19 TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH DI INDONESIA MENGGUNAKAN PENDEKATAN SHARIA MAQASID INDEX (SMI) PERIODE JUNI 2019- JUNI 2020 - Lica Miana; Nonie Afrianty; Asnaini Asnaini (JURNAL AGHNIYA, 2021)
This study aims to analyze the impact of Covid-19 on the financial performance of Islamic banking in Indonesia using sharia maqasid index (SMI) approach reviewed from the objectives of individual education, justice creation, welfare achievement during 2019-2020. This research uses a type of research mix method, which is a combination of quantitative methods and qualitative methods. The population specified in this study is Sharia Commercial Bank (BUS) in Indonesia. The samples used were three banks, namely Bank BRI Syariah, Bank BNI Syariah and Bank Syariah Mandiri. Based on the results of the Covid-19 Pandemic research, the impact on business activities so as to affect financial performance with SMI shows that Bank BNI Syariah has the highest sharia maqasiq index (SMI) score compared to the other two Sharia commercial banks with a score of 1,579